2012
DOI: 10.1155/2012/156035
|View full text |Cite
|
Sign up to set email alerts
|

Features of “All LNA” Duplexes Showing a New Type of Nucleic Acid Geometry

Abstract: “Locked nucleic acids” (LNAs) belong to the backbone-modified nucleic acid family. The 2′-O,4′-C-methylene-β-D-ribofuranose nucleotides are used for single or multiple substitutions in RNA molecules and thereby introduce enhanced bio- and thermostability. This renders LNAs powerful tools for diagnostic and therapeutic applications. RNA molecules maintain the overall canonical A-type conformation upon substitution of single or multiple residues/nucleotides by LNA monomers. The structures of “all” LNA homoduplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…7), suggests that the duplex is adopting a structure at least some-what similar to the poly(rA) parallel double-helix. It has been shown that LNA-RNA (i.e., one strand containing all LNA residues, and the pairing strand having all ribose sugars) antiparallel and Watson-Crick paired duplexes adopt a helical conformation with parameters that are unlike RNA-RNA and LNA-LNA antiparallel duplexes, and resemble an intermediate conformation between the two (Eichert et al 2010;Förster et al 2012). Future structural studies are needed to elucidate the helical parameters of a poly( LNA A)-poly(rA) parallel double-helix that we have identified here; it will be interesting and informative to then contrast and compare poly( LNA A)poly(rA) and poly(rA)-poly(rA) parallel helical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…7), suggests that the duplex is adopting a structure at least some-what similar to the poly(rA) parallel double-helix. It has been shown that LNA-RNA (i.e., one strand containing all LNA residues, and the pairing strand having all ribose sugars) antiparallel and Watson-Crick paired duplexes adopt a helical conformation with parameters that are unlike RNA-RNA and LNA-LNA antiparallel duplexes, and resemble an intermediate conformation between the two (Eichert et al 2010;Förster et al 2012). Future structural studies are needed to elucidate the helical parameters of a poly( LNA A)-poly(rA) parallel double-helix that we have identified here; it will be interesting and informative to then contrast and compare poly( LNA A)poly(rA) and poly(rA)-poly(rA) parallel helical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LNA with 2’fluoro RNA are more stable than 2’OMe RNA counterpart in 10% of foetal bovine serum thus demonstrating their stability [ 17 ]. Interestingly, and in contrast to 2’OMe modifications, multiple LNA residues can be incorporated through the whole oligonucleotides sequence without compromising the base-pairing interaction between the AMOs and the miRNAs [ 16 , 18 ]. This demonstrates that LNAs are one of the most efficient and advanced chemical modification often included in most, if not all miRNA-based oligonucleotide therapies [ 19 ].…”
Section: Design and Chemical Modifications Of Mirna Oligonucleotidesmentioning
confidence: 99%
“…Dabei ist die Helix im Fall der LNA deutlich gestreckter und breiter. [56] RNA LNA erhöht werden (Tm = 4 -8 °C pro Nukleotid). [47,54,57,58] Ein Grund dafür ist, dass die starre Struktur der LNA auch benachbarte Desoxyribosen in die 3´-endo-Konformation zwingt.…”
Section: Locked Nucleic Acids (Lnas)unclassified
“…Dort ist die Helix deutlich gestreckter und breiter als bei der natürlichen RNA (Abbildung 10). [56,59] In Hybrid-Duplices kann dahingegen eine Mischung beider Strukturen beobachtet werden. [56] Aufgrund dieser strukturellen Unterschiede werden LNAs in Proteinkomplexen schlecht toleriert.…”
Section: Locked Nucleic Acids (Lnas)unclassified
See 1 more Smart Citation